Supplementing Resin Production by Tapping Blue Pine (Pinus walllchiana) - Gulati, N. K.; Fernandez, R. R.; Payal, P. S. (Indian Forester, 1983)
Results of experiments in the tapping of Blue pine, carried out at Kanasar in Chakrata Division have revealed that application of stimulants like 2, 4-D, 2,4, 5-T and MCPA prolong the tapping period and thereby increases the resin yield. Trees tapped for full tapping season i.e. April to November yielded 2.1 to 2.28 kg oleo-resin per tree which is definitely an economically viable proposition especially keeping in view the higher pinene contents in the turpentine oil obtained from blue pine oleo-resin which increases its value.